The effect of inhibitors on photosynthetic electron transport chain in canola leaf discs - Emanuela Garbin Martinazzo; Anelise Tessari Perbini; Marcos Antonio Bacarin (Acta Scientiarum. Biological Sciences, 2015)
The mechanisms of photosynthetic electron transport can be elucidated by inhibition of electron flow through the use of specific substances that, when combined with the chlorophyll  chlorophyll a fluorescence emission was measured to investigate the effect of several inhibitors of the photosynthetic electron transport chain in canola leaf discs. Leaf discs were incubated in the dark for 2 hours in different solutions: (a) water – control; (b) DCMU at 500 µM; (c) phenanthroline at 10 mM; and (d) hydroxylamine at 10, 50, 100 and 200 mM. Similar effects were observed between DCMU and phenanthroline, the initial fluorescence value was altered, but not the maximum fluorescence, with the disappearance of the IP phase. Hydroxylamine interacted and inhibited the oxygen evolving complex and caused an imbalance between the rate of QA reduction by photosystem II and the rate of QA oxidation by photosystem I.